Needs and expectations of family caregivers of cancer patients in palliative care: A study protocol - Fernandes, Júlio Belo; Domingos, Josefa; Castro, Cidália; Simões, Aida; Fernandes, Sónia; Almeida, Ana Silva; Bernardes, Catarina; Miranda, Luís; Risso, Sandra; Ferreira, Rogério; Baixinho, Cristina Lavareda; Silvestre, Milene; et al. (Frontiers in Psychology, 2023)
Cancer has an associated burden that continues to grow, affecting patients, family caregivers, and the individual’s community. The family caregivers’ unmet needs may harmfully jeopardize their well-being and the patient’s health outcomes. Therefore, it is essential to understand the needs and expectations of family caregivers of cancer patients to develop and improve care practices. The present study aims to explore the needs and expectations of family caregivers of cancer patients in palliative care. This qualitative, descriptive exploratory study will use purposive sampling to recruit family caregivers and healthcare professionals from the palliative care units of two hospital centers in Lisbon and Tagus Valley. First, the Focus group will be performed until data saturation occurs. Then, a conventional thematic analysis will be applied to analyze data with the help of the coding software QDA Miner Lite database. This study’s findings will help identify gaps in care and provide data that can support healthcare professionals in providing evidence-based centered care to family caregivers. It can also generate knowledge that may help stakeholders to develop a comprehensive support system for cancer survivors in palliative care and their family caregivers.